The demise of works councils in Germany - Susanne Kohaut; Claus Schnabel (Friedrich-Alexander-Universität Erlangen-Nürnberg, Lehrstuhl für Arbeitsmarkt- und Regionalpolitik, 2024)
This paper documents and analyses the demise of works councils in Germany in the period 2007-2022. Using representative panel data, we show that the share of plants with a works council has fallen substantially in the private sector but not in the public sector. Almost two-thirds of workers in the private sector in Germany are not covered by worker co-determination anymore. We present first evidence that firm dynamics (i.e. entries and exits of firms) seem to be one contributory factor to the reduction in works council coverage over time. Multivariate analyses indicate that three variables play an important role in explaining the (non-)existence and the dissolution of works councils. These are plants' decreasing coverage by collective bargaining agreements, the growing relevance of alternative, non-statutory forms of worker representation, and the owner-management of a plant. As our results paint a bleak picture for the future of plant-level co-determination in Germany, we critically discuss a number of policy measures to stabilize works council prevalence. – – Diese Studie dokumentiert und analysiert den Niedergang von Betriebsräten in Deutschland im Zeitraum von 2007 bis 2022. Mit repräsentativen Paneldaten zeigen wir, dass der Anteil der Betriebe mit einem Betriebsrat im privaten (nicht aber im öffentlichen) Sektor deutlich zurückgegangen ist. Fast drei Drittel der Beschäftigten im privaten Sektor werden nicht mehr von der betrieblichen Mitbestimmung erfasst. Wir präsentieren erstmals empirische Evidenz, dass Firmendynamiken (d.h. Einund Austritte von Firmen) zum Rückgang der Verbreitung von Betriebsräten beizutragen scheinen. Multivariate Analysen deuten darauf hin, dass drei Variablen eine wichtige Rolle bei der Erklärung der (Nicht-)Existenz und Auflösung von Betriebsräten spielen. Diese sind die abnehmende Tarifbindung der Betriebe, die zunehmende Bedeutung von alternativen, nicht gesetzlich festgelegten Formen der Arbeitnehmermitbestimmung sowie eigentümergeführte Betriebe. Da unsere Ergebnisse ein düsteres Bild der künftigen betrieblichen Mitbestimmung in Deutschland zeichnen, diskutieren wir kritisch verschiedene Politikmaßnahmen zur Stabilisierung der Verbreitung von Betriebsräten.
Keywords: J53; M50; 330; works council; co-determination; worker participation; Germany